Fully developed forced convection analysis of magneto-hydrodynamic nano fluid through annular sector duct. (December 2021) - Ahmed, Farhan
During this study, we have investigated the effect of magnetic field on heat transfer flow of an electrically conducting magneto-hydrodynamic, ( MHD ) nano fluid through annular sector duct. The problem is formulated under the assumption of fully developed flow by ignoring the deviation of velocity components in the axial direction only; and simulated with the help of semi implicit method for pressure linked equations revised, ( SIMPLER ). The effect of Hartman number, M, on fully developed forced convection flow has been determined for different values of Copper nano particles contribution in base fluid, ϕ, apex angle, β and ratio of radii, Ȓ . With increase in the value of M, a prominent effect has been observed on friction factor, fRe . Furthermore, the influence of nano particles contribution on friction factor, fRe, has been dominated, when we increase the value of M .